2011
DOI: 10.1016/j.biomaterials.2011.04.038
|View full text |Cite
|
Sign up to set email alerts
|

The stimulation of the cardiac differentiation of mesenchymal stem cells in tissue constructs that mimic myocardium structure and biomechanics

Abstract: We investigated whether tissue constructs resembling structural and mechanical properties of the myocardium would induce mesenchymal stem cells (MSCs) to differentiate into a cardiac lineage, and whether further mimicking the 3-D cell alignment of myocardium would enhance cardiac differentiation. The tissue constructs were generated by integrating MSCs with elastic polyurethane nanofibers in an electrical field. Control of processing parameters resulted in tissue constructs recapitulating the fibrous and aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(87 citation statements)
references
References 65 publications
(101 reference statements)
1
85
0
1
Order By: Relevance
“…The resulting viscoelastic parameters (E 1 , E 2 , and g) were significantly higher for the decellularized pcECM than for the native tissue, implying an increased stiffness and apparent viscosity due to decellularization, which is also consistent with the measured increase in the Young's modulus. This increased stiffness, previously reported elsewhere, 7,10,12,55 and demonstrated herein for the decellularized pcECM using both analysis methods, can possibly be attributed to a denser and more compact ECM mainly composed of collagen fibers 10,46,56 as a result of the loss of cellular components. Yet the toe border strain (presented in the Supplementary Data) was similar for both the pcECM and native tissue, implying that the preservation of collagen and nonload-bearing proteins, 41,56 such as elastin, is also consistent with our previously reported results showing a minimal loss of such ECM components during decellularization.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The resulting viscoelastic parameters (E 1 , E 2 , and g) were significantly higher for the decellularized pcECM than for the native tissue, implying an increased stiffness and apparent viscosity due to decellularization, which is also consistent with the measured increase in the Young's modulus. This increased stiffness, previously reported elsewhere, 7,10,12,55 and demonstrated herein for the decellularized pcECM using both analysis methods, can possibly be attributed to a denser and more compact ECM mainly composed of collagen fibers 10,46,56 as a result of the loss of cellular components. Yet the toe border strain (presented in the Supplementary Data) was similar for both the pcECM and native tissue, implying that the preservation of collagen and nonload-bearing proteins, 41,56 such as elastin, is also consistent with our previously reported results showing a minimal loss of such ECM components during decellularization.…”
Section: Discussionsupporting
confidence: 81%
“…The suggested analysis, performed on thick (*15 mm) porcine left ventricle wall cardiac tissue, reveals that although their viscosity and apparent elasticity might be different, the overall viscoelasticity and strength of the decellularized ECM resemble that of native tissue, supporting its utilization in tissue engineering applications. Preliminary studies of decellularized ECM reseeded with human bone marrow mesenchymal stem cells (MSCs), which were previously suggested as model cells and potential progenitors for cardiomyocytes, [46][47][48] reveal that most mechanical properties are partially restored following seeding and cultivation. The complete codes for algorithm implementation along with examples and documentation for the code execution are provided in the Supplementary Data.…”
mentioning
confidence: 99%
“…Their application in myocardial tissue engineering is, however, still in its infancy. In vitro evaluations underpinned the suitability of electrospun membranes for cardiomyocyte guidance and differentiation as well as maintenance of their contractile function [20][21][22]. The fibrous, anisotropic architecture of electrospun scaffolds compared to solid substrates proved superior for cardiomyocyte maturation and, in particular, cell infiltration and multi-layered tissue formation [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…76,77 Additionally, more recently it was found that 3D cellular alignment could significantly promote differentiation of MSCs into cardiomyocytes without using chemical reagents or co-culturing with other cell types. 78 In this work, MSCs were aligned within the 3D structure of elastic tissue constructs. The expression of cardiac markers was significantly promoted by the enhancement in alignment, demonstrating a potential for cardiac regeneration.…”
Section: Directing Stem Cell Differentiation Into Cardiac Lineagementioning
confidence: 99%